Determinan Hasil Belajar AKL SMK N 2 Kota Madiun Pada Kurikulum Merdeka - Oktavia, Dita Refa; Utomo, Supri Wahyudi; Sulistyowati, Nur Wahyuning (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Learning is a way for people to learn about unknown things. Factors within students greatly influence their learning outcomes. Various efforts are made by teachers and students to achieve the best possible learning outcomes. The research aims to examine the influence of the determinants of AKL learning outcomes for class Data was taken through a questionnaire and analyzed using the classic assumption test, multiple linear regression. The research showed that partially and simultaneously the AKL learning outcomes of students at SMK Negeri 2 Madiun City class X were influenced by will, independence and motivation.